In-Hospital Major Adverse Cardiac Events Factor Predictors on ST-Elevation Myocardial Infarction after Primary Percutaneous Coronary Intervention at dr. Cipto Mangunkusumo General Hospital - Sally Aman Nasution; Hendra Perkasa; Eka Ginanjar; Ikhwan Rinaldi (Faculty of Medicine Universitas Indonesia, 2022)
Major Adverse Cardiac Events (MACE) are the main causes to increase mortality in ST-Elevation Myocardial Infarction (STEMI) patients who undergo Primary Percutaneous Coronary Intervention (PPCI). In-hospital MACE inducing factor predictors identification is expected to enhance STEMI patients’ care and outcome. This study aims to identify in-hospital MACE factor predictors in STEMI patients with PPCI treatment at RSCM. Retrospective cohort study by tracing medical records on patients with PPCI treatment at RSCM from January 2015 - March 2020. The chi-squared bivariate analysis concluded between predictor factors; age, smoking, hypertension, diabetic Mellitus, chronic kidney disease, time-to-treatment, Killip class, left ventricle ejection fraction (LVEF) and LDL cholesterol level. Logistic regression is used in multivariate and prediction model analysis on variables with p<0,25 in bivariate analysis. This study involves 291 patient subjects. The occurrence of MACE is 43.3% on patients age > 60 years (29,6%), smoking (61,2%), hypertension (50,9%), diabetes mellitus (36,1%), chronic kidney disease (6,2%), Killip class II-IV (32,2%), LVEF > 50% (57%) dan cholesterol LDL level > 100 mg/dl (79,4%). Median time-to-treatment is 528 (379-730) minutes. Age, Killip class, and LVEF influences in-hospital MACE during PPCI with OR (95% CI) consecutively are 2,15 (1,22-3,79), 4,34 (2,49-7,56) and 2,88 (1,72-4,82). MACE prediction model in this study produces area under curve (AUC) 0,729 (95% CI 0,67-0,78). In-hospital MACE on STEMI patients after PPCI occurrence is 43.3%, influenced by age, Killip class, and LVEF. Keywords: major adverse cardiac events, primary percutaneous coronary intervention, myocardial infarction. Faktor Prediktor Major Adverse Cardiac Events Selama Perawatan pada Pasien ST-Elevasi Miokard Infark yang Menjalani Intervensi Koroner Perkutan Primer di RSUPN dr. Cipto Mangunkusumo Abstrak Major Adverse Cardiac Events (MACE) merupakan penyebab utama meningkatnya mortalitas pada pasien STElevasi Miokard Infark (STEMI) yang menjalani intervensi koroner perkutan primer (IKPP). Identifikasi faktor prediktor yang mempengaruhi terjadinya MACE selama perawatan diharapkan dapat meningkatkan perawatan dan luaran klinis dari pasien STEMI. Penelitian ini bertujuan untuk mengetahui faktor prediktor MACE selama perawatan pada pasien STEMI yang dilakukan IKPP di RSCM. Studi kohort retrospektif dengan menelusuri rekam medis pasien yang menjalani IKPP di RSCM periode Januari 2015-Maret 2020. Dilakukan analisa bivariat antara faktor prediktor usia, status merokok, hipertensi, diabetes mellitus, penyakit ginjal kronik, time-to-treatment, kelas killip, fraksi ejeksi ventrikel kiri (FEVK) dan kadar kolesterol LDL dengan kejadian MACE selama perawatan pada pasien STEMI yang menjalani IKPP, menggunakan metode Chi-square. Analisa multivariat dan analisa model prediksi dilakukan dengan metode regresi logistik terhadap variabel dengan nilai p= <0,25 pada analisa bivariat.Didapatkan subyek sebanyak 291 pasien untuk diteliti. Major Adverse Cardiac Events selama perawatan didapatkan sebesar 43,3% dengan usia >60 tahun (29,6%), status merokok (61,2%), hipertensi (50,9%), diabetes mellitus (36.1%), penyakit ginjal kronik (6,2%), kelas Killip II-IV (32,2%), FEVK > 50% (57%) dan kadar kolesterol LDL > 100 mg/dl (79,4%). Median timeto-treatment didapatkan sebesar 528 (379-730) menit. Usia, kelas killip dan FEVK mempengaruhi kejadian MACE selama perawatan dengan OR (IK 95%) masing-masing 2,15 (1,22-3,79), 4,34 (2,49-7,56) dan 2,88 (1,72-4,82). Model prediksi MACE selama perawatan pada pasien STEMI yang menjalani IKPP memiliki nilai area under curve (AUC) 0,729 (IK 95% 0,67-0,78). Major Adverse Cardiac Events (MACE) selama perawatan Kata kunci: major adverse cardiac events, intervensi koroner perkutan primer, infark miokard.